Digital Literacy and Technostress in the Job Demands–Resources Perspective: The Mediating Role of Instructional Innovation on Elementary School Teachers’ Performance - Fahriansyah Fahriansyah; Rizky Fauzan; Titik Rosnani (Business and Applied Management Journal, 2025)
This study examines the influence of digital literacy and technostress on elementary school teachers’ performance with instructional innovation as a mediating variable within the Job Demands–Resources (JD-R) framework. The research employed a quantitative explanatory design using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from elementary school teachers in West Kalimantan Province through an online questionnaire. The results indicate that digital literacy has a significant positive effect on instructional innovation and teachers’ performance. Instructional innovation also significantly improves teachers’ performance. Meanwhile, technostress does not have a direct effect on teachers’ performance but does influence it indirectly through instructional innovation. These findings suggest that digital literacy functions as an important job resource that enhances innovative teaching practices. In contrast, technostress can act as a challenge that stimulates adaptive innovation in digital learning environments. The model demonstrates strong explanatory power with an R² value of 0.706 for teachers’ performance. The study contributes to the development of JD-R theory in digital education by identifying instructional innovation as an adaptive mechanism that transforms job demands and job resources into improved teacher performance.